Geophysical characterization of liquefaction-prone areas: The Quistello test site, central Po Plain, Northern Italy. Issue 116 (January 2019) - de Franco, R.; Caielli, G.; Mollica, R.; Norini, G.; Aghib, F.S.; Di Capua, A.; Boniolo, G.; Corsi, A.; Piccin, A.; Facciorusso, J.; Martelli, L.
Abstract: A geophysical conceptual model for sites prone to seismic liquefaction is presented, introducing a geophysical protocol to characterize the liquefaction proneness. Three parameters are used to characterize homogeneous units: v s, a proxy of the geotechnical classes of soils, v p related to the saturation degree and v p / v s ratio, related to the liquefaction geophysical susceptibility. A layer is geophysically susceptible to liquefaction when it meets the following criteria: a) v s < 270 m/s and 1300 < v p < 1800 m/s; b) v p / v s > 5. The model has been tested and validated in the Quistello site, where liquefaction occurred during the 2012 Emilia earthquake. The validation of the proposed geophysical model for liquefaction susceptibility against the geotechnical one, calculated from CPTU, indicates the reliability of the proposed approach. This approach was extended to other sites affected by the 2012 seismic swarm. The study demonstrates that the geophysical susceptibility to liquefaction could be an indicator to support microzonation studies concerning the liquefaction proneness of extended areas. Highlights: A geophysical conceptual model for sites prone to seismic liquefaction and a geophysical protocol to characterize the liquefaction proneness of a site are proposed. A subsurface unit could be geophysically susceptible to liquefaction when are verified these conditions: a) v s < 270 m/s and 1300 < v p < 1800 m/s; b) v p / v s > 5. An agreement between geophysical and geotechnical surveys has been found after the comparison with liquefaction potential indexes belonging to cone penetration tests. A detailed liquefaction assessment has been conducted in the Quistello site and then applied to other Po valley sites affected by the 2012 Emilia earthquake (North Italy). The Holocene sites were found to be more susceptible to liquefaction than Pleistocene sites.